Pedagogical Practice in the Process of Complex Preparation of Students for Professional Activity - Sh.N. Ibadullayeva (Zien Journals, 2023)
In this article discusses about pedagogical practice in the process of complex preparation of students for professional activity
Keywords: globalization; professional; modernization